Nepal’s Education Paradox: Expanding Access, Limited Completion and Learning - Subedi, Tekraj (An ENDEAVOUR: Journal of Academia and Research, 2026)
Nepal has made substantial progress in the primary and lower-secondary school enrollment in the last two decades. Yet these enrollment expansions have not translated into improvements in school completion, progression, or learning. This paper uses the 2021 administrative data from the Center for Education and Human Resource Development (CEHRD, 2021) to highlight this difference. First, we show high enrollment in the early grades, which falls sharply at the secondary and upper-secondary levels. The decline is steeper in disadvantaged provinces and social settings. Second, we study the associations between student-teacher ratios and key schooling outcomes. These patterns do not establish causality, but they do suggest that access by itself is not enough. A durable improvement in human capital will require greater attention to retention, progression, and the quality of schooling, alongside targeted support for students facing the greatest barriers.